Consumers and citizens : globalization and multicultural conflicts - García Canclini, Néstor (Cultural studies of the Americas ;, 2001)
The best-known and most innovative cultural studies scholar in Latin America maps the critical effects of urban sprawl and global media and commodity markets on citizens--and shows at the same time that the complex results mean not only a shrinkage of certain traditional rights (particularly those of the welfare or client state) but also new openings for expanding citizenship.